Isolation of Fission Yeast Condensin Temperature-Sensitive Mutants with Single Amino Acid Substitutions Targeted to Hinge Domain. Issue 5 (1st May 2019) - Xu, Xingya; Yanagida, Mitsuhiro
Abstract: Essential genes cannot be deleted from the genome; therefore, temperature-sensitive (ts) mutants and cold-sensitive (cs) mutants are very useful to discover functions of essential genes in model organisms such as Schizosaccharomyces pombe and Saccharomyces cerevisiae . To isolate ts/cs mutants for essential genes of interest, error-prone mutagenesis (or random mutagenesis) coupled with in vitro selection has been widely used. However, this method often introduces multiple silent mutations, in addition to the mutation responsible for ts/cs, with the result that one cannot discern which mutation is responsible for the ts/cs phenotype. In addition, the location of the responsible mutation introduced is random, whereas it is preferable to isolate ts/cs mutants with single amino acid substitutions, located in a targeted motif or domain of the protein of interest. To solve these problems, we have developed a method to isolate ts/cs mutants with single amino acid substitutions in targeted regions using site-directed mutagenesis. This method takes advantage of the empirical fact that single amino acid substitutions (L/S -> P or G/A -> E/D) often cause ts or cs. Application of the method to condensin and cohesin hinge domains was successful: ∼20% of the selected single amino acid substitutions turned out to be ts or cs. This method is versatile in fission yeast and is expected to be broadly applicable to isolate ts/cs mutants with single amino acid substitutions in targeted regions of essential genes. 11 condensin hinge ts mutants were isolated using the method and their responsible mutations are broadly distributed in hinge domain. Characterization of these mutants will be very helpful to understand the function of hinge domain.